The army nurse - Scerri, Mariella (Research and Humanities in Medical Education, 2020)
Storied accounts of nurses’ representations on the battlefield become vital records of personal or communal histories that otherwise may not be voiced or even acknowledged. What we have today is a fairly accurate account of the harsh realities nurses endured at the battlefield and how these horrific situations shaped them as nurses who would act as role models in the brink of death. While women’s writing about war has received much critical attention that has established its authenticity as witness to war, scant attention has been paid to how women see the trauma of nursing at the frontline and how it influences the narrative. The scope of this article is to understand the connections between nurses’ narratives from the First World War and Vietnam. It tries to elicit common elements in how war is seen and consequently to the relationship between seeing and bearing witness to wars.